An Interactive Mobile Application to Request the Help of the Nearest First Aider by the Injured: The Design and Implementation of an Interactive Mobile Application to request the help of the nearest first aider by the injured - Alshutayria, Areej; Aljojo, Nahla; Alharbia, Basma; Banjarb, Ameen; Alshehria, Atheer; Alargoubia, Mashaiel; Barradha, Ola; Helabia, Rahaf (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2021)
Saudi Arabia is interested in providing health care and ambulatory for all citizens, residents and tourists of the pilgrims and pilgrims, and it is cooperating with the Saudi Red Crescent Authority (SRCA) to provide emergency health care especially for the pilgrims, Ammar - an independent body dealing with this. The efforts of SRCA can be highly noticed during on the Hajj season and public events such as the national day celebrations. The main issue lies in the fact that despite their efforts, the Ambulance Response Time (ART) remains higher than the global standard. Moreover, the reasons behind the high ART are circumstantial and thus hard to maneuver or manipulate. Therefore, to benefit from the Red Crescent’s efforts and the first aid courses they offer, a system where credible first aiders can be summoned to provide proper and faster first aid to the injured is suggested. This study aims to develop an application to request the help of the nearest first aider by the injured or bystanders close to the injured. Also, to develop an interface that shows the route to get to the victim. The result has shown a positive indication of the importance of a system where credible first aiders can be summoned to provide proper and faster first aid to the injured. This study contributes to increase bystanders’ awareness because they have the ability to connect with the nearest registered first aider.